MENINGKATKAN EFEKTIVITAS BELAJAR LEMPAR CAKRAM DENGAN MENGGUNAKAN MEDIA MODIFIKASI PIRING PLASTIK - Ribain Ribain (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2018)
The general purpose of this study was to improve the effectiveness of learning discus throwing in the sixth grade of Puter I State Elementary School, Kembangbahu District, Lamongan Regency. The specific purpose is to find out the extent of (1) student activity in learning, (2) teacher activities in teaching, (3) student responses to learning, and (4) learning outcomes of throwing discs with modification media on plastic plates. The subjects of this class action research were the sixth grade students of Puter I State Elementary School with a total of 13 female students and 15 male students, so the total number of 28 students. The procedure or steps taken in the form of a research cycle consisting of four main activities: planning, action, observation, and reflection. Research data collection is done by determining the data source first, then the type of data, data collection techniques, and instruments used. The results of the study showed that student activities, teacher teaching activities, and the average learning completeness of students increased.